1983
DOI: 10.1079/bjn19830130
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal role of milk folate-binding protein: studies on the course of digestion of goat's milk folate binder in the 6-d-old kid

Abstract: 1. Groups of kids were reared from birth to 5 d on goat's milk. On the 6th day five of the kids received by bottle a morning feed of goat's milk with [3H]folic acid added to saturate the folate-binding proteins (FBP) (Expt 1); three kids received raw goat's milk containing only the endogenous folate and hence a large surplus folate-binding capacity (FBC) (Expt 2). The contents of the stomach, duodenum, jejunum and ileum were recovered by washing out 1·5 h after feeding (Expt 1) or at 0·5, 1 and 3·5 h after fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…FBP is present in different biological, secretory fluids, including saliva and semen, and in particular milk [4][5][6][7][8][9]. The significance of these folate binders is largely unknown, but it has been suggested that milk FBP, shown to be resistant to gastric digestion [27], may play a role in folate uptake in the neonate intestine [10][11][12]. The present study shows that megalin, a large, multiligand, endocytic receptor expressed in the intestine and other absorptive epithelia binds and mediates the internalization of FBP.…”
Section: Discussionmentioning
confidence: 99%
“…FBP is present in different biological, secretory fluids, including saliva and semen, and in particular milk [4][5][6][7][8][9]. The significance of these folate binders is largely unknown, but it has been suggested that milk FBP, shown to be resistant to gastric digestion [27], may play a role in folate uptake in the neonate intestine [10][11][12]. The present study shows that megalin, a large, multiligand, endocytic receptor expressed in the intestine and other absorptive epithelia binds and mediates the internalization of FBP.…”
Section: Discussionmentioning
confidence: 99%
“…mFBPs have been found in tissues from placenta (4, 6, 17, 25, 60,89,90), proximal kidney tubules (13, [77][78][79][80][81], choroid plexus (86), small intestine (79), and liver (14). sFBPs are present in human (3,7,58,76,87,94), bovine (7,26,87,88), and goat (66,72) milk, in the growth medium from human KB cells (18,45) and cultured human lympho cytes (15), in normal human serum (57,93), and in umbilical cord serum (43). Milk and umbilical cord serum are relatively abundant sources of sFBP, whereas relatively low levels of sFBP occur in normal serum (43,92).…”
Section: Distributionmentioning
confidence: 98%
“…The mechanism of sequestering folate in human milk is very efficient, since lactation alone causes a decrease in maternal folate status (58,84) and can cause maternal folate deficiency (56). Studies in 6-day-old goat kids (72) showed that the FBP of goat milk is resistant to proteolysis by pancreatic enzymes and can survive along the length of the small intestine. Protease inhibitors inherent to milk may also assist the passage of intact binders into the small intestine (51).…”
Section: Milk Folate-binding Proteinsmentioning
confidence: 99%
“…This situation was demonstrated by Salter & Mowlem (1983) who showed that a proportion of goat's milk FBP administered orally to neonatal goats survived along the length of the small intestine. In neonates, the uptake of folate bound to milk FBP occurs preferentially in the ileum as opposed to the jejunum.…”
Section: Absorption Of Milk Folate By the Suckling Infantmentioning
confidence: 95%